Ursodeoxycholic acid induced skin eruption: a case report - James, Anna; M., Indhupriyadharshini; M., Anjali; Premkumar, Sivaraman (International Journal of Research in Medical Sciences, 2024)
This case report discusses a rare adverse reaction associated with ursodeoxycholic acid (UDCA), highlighting its potential impact on patient management and treatment outcomes. UDCA, commonly used for gallstone dissolution and liver disease, occasionally induces skin eruptions, though mechanisms remain unclear. A 23-year-old male with a history of jaundice and fatty liver presented with a right inguinal hernia. He was prescribed UDCA (300 mg), among other medications, post-surgical intervention. Twelve hours later, he developed sharply demarcated, dusky red plaques on his hands, suggestive of a type IV delayed hypersensitivity reaction. The Naranjo score indicated a probable association between UDCA and the skin eruption. Discontinuation of UDCA led to gradual resolution of symptoms. This case underscores the importance of recognizing and managing rare adverse reactions to UDCA, such as dermatological manifestations. While typically non-life-threatening, these reactions can necessitate treatment discontinuation, potentially compromising therapeutic efficacy. Vigilant monitoring and further research are essential to elucidate underlying mechanisms and optimize patient care strategies.